2006
DOI: 10.1029/2006gl026507
|View full text |Cite
|
Sign up to set email alerts
|

Small slow‐strain steps and their forerunners observed in gold mine in South Africa

Abstract: [1] The Research Group for Semi-controlled Earthquakegeneration Experiments in South African deep gold mines (SeeSA) has continuously monitored strain changes with a resolution of 24 bit 25 Hz at the Bambanani mine near Welkom. An Ishii borehole strainmeter was installed at a depth of 2.4 km near the potential M $ 3 earthquake source area. Instantaneous strain steps of $10 À4 strains associated with two M2 events were observed within a length of seismic fault. These steps were followed by significant postseism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The result of this study indicates the possibility of frequency-dependent increase in the seismic attenuation of transmitting waves through a fault zone before earthquakes. Naoi et al (2006) reported that aseismic slow strain steps were observed in the vicinity of the M ∼ 2 focal regions, and that these Figure 10. Normalized relative spectral amplitudes for all earthquake pairs of interest (dark grey for seismograms of events marked with asterisk in Table 1 and light grey for stacked waveforms) and synthetic ones calculated with suitable values of a and ( ε 2 ) 1/2 (black).…”
Section: Frequency Dependent Pre-seismic Changes In S-wave Attenuationmentioning
confidence: 90%
See 2 more Smart Citations
“…The result of this study indicates the possibility of frequency-dependent increase in the seismic attenuation of transmitting waves through a fault zone before earthquakes. Naoi et al (2006) reported that aseismic slow strain steps were observed in the vicinity of the M ∼ 2 focal regions, and that these Figure 10. Normalized relative spectral amplitudes for all earthquake pairs of interest (dark grey for seismograms of events marked with asterisk in Table 1 and light grey for stacked waveforms) and synthetic ones calculated with suitable values of a and ( ε 2 ) 1/2 (black).…”
Section: Frequency Dependent Pre-seismic Changes In S-wave Attenuationmentioning
confidence: 90%
“…Naoi et al. (2006) reported that aseismic slow strain steps were observed in the vicinity of the M ∼ 2 focal regions, and that these aseismic slow strain steps increased after FebM2 and increased at a greater rate after AprM2.…”
Section: Temporal Changes In the S‐wave Attenuationmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper presents our analysis of the seismicity around an advancing mining front using AE monitoring data in the Cooke 4 Mine (previously known as the Ezulwini Gold Mine) in South Africa. Deployed as part of the Science and Technology Research Partnership for Sustainable Development (SATREPS) program, [15][16][17][18][19][20] sensors have located AEs as small as À 4 in moment magnitude (M w ) or even smaller. We applied the joint hypocenter determination (JHD) method 21 to these AE data to improve the absolute location accuracy followed by the double difference (DD) method 22 to improve the relative location accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…meters (Takeuchi, 2005;Naoi et al, 2006) and several-kHz frequency-band seismometers (Yamada et al, 2005(Yamada et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%